(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This article explores the system of protecting children’s rights based on international and national legal documents. The UN Convention on the Rights of the Child, its optional protocols, and relevant legislation of the Republic of Uzbekistan are analyzed. The article highlights mechanisms for ensuring effective protection of children’s rights through the harmonization of international conventions and national legislation.